Factors Affecting Online Services Shopping Behavior: A Study of Egyptian Consumers - El-Tahawy, Manal Hamdi (AUC Knowledge Fountain, 2019)
Online services are a relatively new type of shopping in Egypt. Online Service (e-service) is defined as an experience or act delivered by one person to another, being requested online, and delivered online or offline, without this second person owning any tangible product. This type of shopping is overwhelming in the whole world including Egypt. In Egypt, nowadays, the online shopping trend is booming rapidly. A lot of people shop online for nearly all kinds of products and services, yet there are still some products such as buying gold that are not as well bought online as other products and services. There are a lot of factors affecting the behavior of consumers, but most of these factors have not been investigated. Several articles and researches have been conducted on the factors behind online shopping worldwide, but they are very few articles which focus on Egypt and discuss consumers’ online shopping triggers in Egypt. Since Egypt is relatively a collectivist country; it is important to study and to highlight the triggers behind Egyptian consumers online shopping behavior. Thus, this research aims to understand the Egyptian online services shoppers’ behavior behind online shopping for services. Research Design In this research, a descriptive research methodology is used to examine certain traits of a specific group of people (online services shoppers), and to forecast what motivates their online services shopping behavior. To answer this, an obvious research question and set of hypotheses are used. Moreover, since a descriptive research method is used in this research; some quantitative results would be collected through a questionnaire that is distributed over 404 respondents are integrated in the research as the targeted sample and they will be asked some questions and required to answer on a 5-point Likert scale ranging their responses from 1 strongly disagree to 5 strongly agree. Moreover, some demographic questions will be asked at the end of the survey. Key Findings Once all the questionnaires had been filled, then data analysis process started. In data analysis process, the SPSS spread sheet is used to generate all respondents’ responses frequencies and percentages on each question of the survey. Finding shows that 70% of the sample or 283 out of 404 respondents were mainly youth between the age of 18 to 29 years old. Moreover, gender is equally shared in the sample between females who were 50.2% and males who were 49.8% of the sample. Furthermore, 70.3% of the sample respondents were B¬¬achelor degree holders. Reliability is tested to be high since all the independent variables’ Cronbach Alpha including attitude, subjective norm, perceived behavioral control, behavioral intention, desired consequence (convenience, time, price, and trust) ¬¬¬¬¬are above 0.70, so they are all affecting the dependent variable which is online buying intention. Moreover, Findings shows that all independent variables have positive correlation with the dependent variable “Behavior Intention”, yet one independent variable “Attitude” has the highest Pearson Correlation at .691 with the dependent variable “Behavioral Intention”. Furthermore, for the inferential analysis, multiple regression is used for interval hypothesis ANOVA is used to analyze ordinal hypothesis which tackles with demographics, and t-test is used for hypothesis that deals with gender. As a result of the previous, it is concluded that hypotheses 1, 3, 4, 6, 7 and 8 are accepted with “Attitude” being higher predictor for “Behavioral Intention” toward online services shopping followed by “Perceived Behavioral Control”, “Desired Outcome – Trust”, “Desired Outcome – Convenience”, and “Desired Outcome – Price”, beside women having lower “Behavior Intention” to acquire services online than men. Unlike hypotheses 2, 5, 9, and 10 are rejected as the p-value for subjective norm, time, education level, and age group are all above 0.05. Conclusion and Recommendations Results of this research showed that the factors that mainly affect Egyptian online buying intention for online services are attitude, perceived behavioral control, desired outcome including trust, convenience, price. Besides, findings show that women having lower behavior intention to acquire services online than men. On the other hand, findings indicate that respondents also agree that factors such as subjective norm, time, education level, and age group are not determinants of consumers’ buying intention. Based on the research findings, these outcomes will be useful in giving new insights to marketers marketing strategies when examining factors that affect consumers online buying intention in business-to-consumer fields. Hence, marketers would be able to ¬¬¬¬¬¬¬increase their business value and compete in the market. Moreover, results of this research would be helpful for sellers and shoppers as sellers will be able to boost their selling process by moving to the Internet channels for better and various online services which satisfy their customer for having numerous online services.